UTILIZING POINT-OF-CARE ULTRASOUND FOR ACCURATE IDENTIFICATION OF INFECTION SOURCE IN SEPTIC PATIENTS - KHALID, MA; NAWADAT, Q; MAZHAR, H (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to evaluate the point of care ultrasound to identify the sepsis source in septic patients. A prospective study was conducted in the Emergency Medicine Department of Shifa International Hospital from May 2021 to May 2022. A total of 200 patients who met the SSC criteria were included in the study. The source of sepsis was identified, followed by a diagnostic workup and treatment interventions (T0). The physician who performed the clinical assessment performed a point-of-care ultrasound within 10 minutes and recorded a POCUS-implemented diagnosis (T2). After patient discharge, two physicians blinded to POCUS results reviewed the patient data and recognized the septic source (T2). The source of sepsis was detected in 188 patients (94%), and 12 patients (6%), a specific source could not be identified. POCUS diagnosis detected septic sources in 140 patients with a 74.5% sensitivity. Compared to T2, clinical impressions after T0 had 47% sensitivity and 85% specificity, 90 identified sources, and 5 false positives. POCUS is an accurate and fast diagnostic tool to assess the cause of infection in septic patients compared to a standard workup.